2007
DOI: 10.1097/01.hmr.0000267793.47803.41
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' intent to leave the profession

Abstract: In today's environment of low reimbursement and high cost containment, health care managers need to focus on those items that will have the greatest impact on retaining high-quality nurses because nurses "make the critical, cost-effective difference in providing safe, high-quality patient care."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 7 publications
1
16
2
Order By: Relevance
“…Gender relations in nursing have been gaining increasing attention in the specialist literature—both because historically the profession is associated with women [34] and because of men’s increasing participation in the profession [35]. Borkowski et al [36] observed greater job dissatisfaction among the men in their sample: the authors found that in their job, male nurses encountered more resistance from those in leadership positions, female colleagues, and patients. Evans & Frank [34] observed that male nurses live in constant defence of their professional choice, their value to nursing, and their sexuality.…”
Section: Discussionmentioning
confidence: 99%
“…Gender relations in nursing have been gaining increasing attention in the specialist literature—both because historically the profession is associated with women [34] and because of men’s increasing participation in the profession [35]. Borkowski et al [36] observed greater job dissatisfaction among the men in their sample: the authors found that in their job, male nurses encountered more resistance from those in leadership positions, female colleagues, and patients. Evans & Frank [34] observed that male nurses live in constant defence of their professional choice, their value to nursing, and their sexuality.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Pay and other benefits have been shown to influence nurses' intent to leave an organization and is more important for males than females. [23] However, Frijters et al reported that an increase in nurses' pay had a low impact on retention rates, which suggests that an increase in pay alone will not solve the organizational turnover issue. [31] 1.1.5 Job satisfaction Job satisfaction can be defined as the extent to which an employee likes his or her job.…”
Section: Social Work Environmentmentioning
confidence: 99%
“…Master's degree) may have higher levels of professional commitment, and are therefore less likely to leave the profession. [22,23] …”
Section: Individual Factorsmentioning
confidence: 99%
“…This also seems to be a common trend in comparable studies, where fewer men than women responded to follow-up questionnaires [73-76]. One possible explanation for the smaller number of male respondents could be linked to findings showing that men differ from women in that they: less often enter nursing as a first choice [77], less often complete their education [56,78], have a more critical view towards nursing education [58] and are more inclined to leave the profession [79,80]. As a result, men can be assumed to be less interested in participating in a study directly addressing nursing issues.…”
Section: Methods Discussionmentioning
confidence: 99%